Analysis of Influence Factors Labor Supply Class Elderly at Medan City - Widya Kartika; Ahmad Albar; Irsad Lubis (Lafadz Jaya Publisher, 2023)
This research is to analyze the factors that influence the supply of elderly workers in the city of Medan. Latent variables are divided into two, namely endogenous and exogenous latent variables. This study aims to determine the effect of exogenous latent variables on endogenous latent variables. This study aims to determine the effect of the supply of elderly workers in the city of Medan, such as education, health, income, dependents and employment status. The type of data in this study is primary data obtained directly in the field, namely elderly workers (60 years and over) who are still working in the city of Medan, totaling 271 people. In this study the method used is PLS-SEM with SmartPLS software. Testing in PLS-SEM includes: 1) Testing the outer model (measurement model). 2) Testing the inner model (structural model). The results of the study show that all variable indicators are significant. In the subsequent analysis, this study used significant indicators and showed that all variables had an effect on the supply of the elderly in Medan City. The results of bootstrap estimation for hypothesis testing also conclude that the variables of education, health, income, dependents, employment status have a positive effect on the supply of labor for the elderly in Medan City.